AKTIVITAS ANTIDIABETES DARI BERBAGAI Genus Momordica SECARA IN VIVO - Mella Afita; Nani Wijayanti Dyah Nurrahman; Giftania Wardani Sudjarwo (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Diabetes mellitus (DM) is a chronic disease in the form of metabolic disorders where blood glucose levels are above normal limits. The example of the plants which can reduce blood glucose is Genus Momordica, there are 3 plants from the Genus Momordica, namely Momordica charantia, Momordica cymbalaria and Momordica dioica which contains the most common compounds found, namely saponins and charantin. This study aims to examine the presence of antidiabetic activity from various Momordica genus in vivo. The content of Saponins in the Genus Momordica works by inhibiting the work of the enzyme Î±-glucosidase, which is an enzyme in the intestine that functions to convert carbohydrates into glucose. The second content is charantin. Charantin works by stimulating the beta cells of the pancreatic gland to produce more insulin and increase glycogen reserves in the liver. From the literature review conducted, it can be concluded that plants from the momordica Genus, namely Momordica charantia, Momordica cymbalaria, and Momordica dioica contain saponin and charantin compounds that have the potential to be antidiabetics or reduce blood glucose levels in vivo.